2008
DOI: 10.1152/jn.90563.2008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Increased Activation of Persistent Inward Currents in Individuals With Chronic Hemiparetic Stroke

Abstract: Despite the prevalence of hyperactive stretch reflexes in the paretic limbs of individuals with chronic hemiparetic stroke, the fundamental pathophysiological mechanisms responsible for their expression remain poorly understood. This study tests whether the manifestation of hyperactive stretch reflexes following stroke is related to the development of persistent inward currents (PICs) leading to hyperexcitability of motoneurons innervating the paretic limbs. Because repetitive volleys of 1a afferent feedback c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 59 publications
6
71
0
Order By: Relevance
“…Much of the current evidence regarding alterations in intrinsic electrical properties and subsequent windup behavior following injury to the nervous system has focused on MNs (human: Gorassini et al 2004;McPherson et al 2008;Mottram et al 2009;animal: Bennett et al 1998aanimal: Bennett et al , 1998banimal: Bennett et al , 2001Lee and Heckman 2001;Li et al 2004). Indirect measurements from this study are consistent with a plateau-driven windup response for several reasons.…”
Section: Discussionsupporting
confidence: 63%
“…Much of the current evidence regarding alterations in intrinsic electrical properties and subsequent windup behavior following injury to the nervous system has focused on MNs (human: Gorassini et al 2004;McPherson et al 2008;Mottram et al 2009;animal: Bennett et al 1998aanimal: Bennett et al , 1998banimal: Bennett et al , 2001Lee and Heckman 2001;Li et al 2004). Indirect measurements from this study are consistent with a plateau-driven windup response for several reasons.…”
Section: Discussionsupporting
confidence: 63%
“…As discussed in the following text, these novel findings together suggest that the lower-threshold for stretch reflexes observed in spastic-paretic stroke survivors, while at rest (Chardon et al 2008;Powers et al 1988), in addition to the enhanced tonic vibration reflex (TVR) (McPherson et al 2008) may not be attributable to increases in motoneuron PIC amplitude, yet rather the result of a low-level depolarizing synaptic drive to the resting motoneuron pool.…”
Section: Discussionmentioning
confidence: 80%
“…Such abnormal co-activations have been shown between shoulder abductors with elbow flexors and shoulder adductors with elbow extensors [1,2,3,4,5]. One of the hypothesized neural mechanisms underlying these abnormal muscle co-contraction patterns is an increased reliance on brainstem pathways [6]. In animal studies, Magnus and de Kleijin [7] reported postural reflex patterns, i.e.…”
Section: Introductionmentioning
confidence: 99%